Translations of policy and shifting demands of teacher professionalism: from CPD to professional learning. Issue 3 (3rd May 2016) - Watson, Cate; Michael, Maureen K.
Abstract : This article concerns policy implementation and examines the processes of translation through which policy may be enacted at local level. In particular, it focuses on education policy and constructions of teacher professionalism, drawing on a framework of critical logics – social, political and fantasmatic – which examine different dimensions of social reality. Social logics describe practices, and particularly the 'rules' which govern practices, in a given social domain; political logics are diachronic, enabling an examination of the ways in which practices are contested and/or change over time; fantasmatic logics concern ideologies and the interpellation of subjects into discourses. The linguistic focus of this approach is supplemented by a sociomaterial analysis which examines the materialities inherent in these processes. The article takes as its case a political moment in Scotland in which the discursive context for teacher professional development is undergoing a shift from continuing professional development to professional learning. Here, we analyse the language and material practices of those charged with organising teacher professional development in four local authorities in Scotland. This case is used to explore linguistic and material enactments of policy as a series of translations in which practices emerge and unfold in unpredictable ways.